CP-134 Analysys of therapeutic response and tolerability in patients treated with crizotinib in ALK positive NSCLC. (14th February 2016) - Tonelli, M; Scaldaferri, M; Barilà, D; Bianco, A; Ferroni, M; Valinotti, G; Caiazza, E; Bordignon, S; Martinetto, D; Cattel, F
Abstract : Background: Anaplastic lymphoma kinase (ALK) is a validated tyrosine kinase target in several cancers. Crizotinib is indicated for the treatment of adults with previously treated ALK positive advanced non-small cell lung cancer (NSCLC), which is a distinct molecular subtype of NSCLC. Purpose: Evaluation of the therapeutic efficacy and tolerability of crizotinib in a cohort of 16 previously treated ALK positive advanced NSCLC patients. Material and methods: Evaluation of data from medical records and Italian 'Registro dei Farmaci AIFA'. Results: 56% of patients were female, mean age at diagnosis was 52.5 years and 62.5% were smokers. The histological type was adenocarcinoma for all patients, and 81.25% presented with NSLC stage IV. 93% of patients had previously received platinum based chemotherapy and 18.75% underwent radiotherapy for metastatic disease. Time elapsed between diagnosis and the first treatment with crizotinib was 15.5 months (range 2–101.5). The average treatment duration with crizotinib was 4.2 months with a median dose of 473 mg/day due to interruptions during therapy. The end of treatment was due to progression of disease in 54.54% of cases, in 18.2% to toxicity and not valued in 27.3%; in 9.09% of patients the better response during treatment was assessed as partial response, in 45.45% as stable disease and in 45.45% was not valued. Liver toxicity (rise in liver enzymes: ALT 1106, AST 639), gastrointestinal toxicity and dysgeusia were reported in 4 patients (36.4%). 82% of patients were treated with subsequent therapy, while 27.3% entered Named Patient Programmes for ceritinib and alectinib. Conclusion: Presently, our experience in the treatment of NSCLC with crizotinib is based on a small number of patients. The results showed good tolerance towards the drug. However, this proved to be not effective. References and/or Acknowledgements: Shaw AT, et al . Crizotinib versus chemotherapy in advanced ALK-positive lung cancer. N Engl J Med 2013;368:2385-94 No conflict of interest.